2022
DOI: 10.3390/biom13010014
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme Inhibitor 2-Deficient Mice Exhibit Altered Brain Polyamine Levels and Reduced Locomotor Activity

Abstract: Background: Alterations in the neural polyamine system are known to be associated with different brain pathological conditions. In addition, the regulation of enzymes involved in polyamine metabolism such as ornithine decarboxylase (ODC), antizymes (AZs), and antizyme inhibitors (AZINs) is critical during brain development. However, while most studies focus on ODC and AZs, less is known about AZIN expression and function in the brain. Thus, our aim was to analyze the expression pattern of AZIN2 during postnata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Overall, our analysis established that AZIN1 serves as a key regulator of the Module 2 [Figure 3a]. These results are in strong agreement with other studies in which AZIN1 is shown to play an important role in cancer progression through increasing ornithine decarboxylase activity to accelerate the formation of intracellular polyamine [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, our analysis established that AZIN1 serves as a key regulator of the Module 2 [Figure 3a]. These results are in strong agreement with other studies in which AZIN1 is shown to play an important role in cancer progression through increasing ornithine decarboxylase activity to accelerate the formation of intracellular polyamine [34,35].…”
Section: Discussionsupporting
confidence: 91%
“…90 More recently, transgenic mice deficient in AZIN1 and AZIN2 genes have also been developed. [91][92][93] The in vitro and in vivo observations described above provided the scientific basis for our own hypothesis that patients with BABS having a premature stop codon within the C-terminal destabilization domain of ODC may not be able to fully clear ODC protein through the ubiquitin-independent proteasomal degradation pathway. Consequently, we expected to find accumulated ODC protein that remains functionally active, 87 because the Cterminal mutation does not affect the enzyme's activity center.…”
Section: Odc1 F U Nc Tions a N D Pote N Ti A L Tr E Atm E N T Of Ba Bsmentioning
confidence: 96%
“…SSAT‐1 , AMD1 , SMS , AZ , ARG2 ) have been developed and are summarized in this review 90 . More recently, transgenic mice deficient in AZIN1 and AZIN2 genes have also been developed 91–93 …”
Section: Odc1 Functions and Potential Treatment Of Babsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, AZIN2 has been found increased in brains affected by Alzheimer’s disease [ 79 , 80 ] and its depletion leads to a reduction in Put levels, which is associated with alterations in motor function. These observations imply a role for AZIN2 in the regulation of dopaminergic neuron function [ 81 ].…”
Section: Polyamines Generalitiesmentioning
confidence: 99%